Short-term severe low energy availability in athletes: molecular mechanisms, endocrine responses, and performance outcomes - a narrative review - Jeppesen, J. S.; Hellsten, Y.; Melin, A. K.; Hansen, M. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Many athletes and coaches believe that reducing body mass can improve the power-to-body mass ratio and improve exercise performance. This narrative review aims to characterize the effects of short-term (days to weeks) severe (< 30 kcal/kg Fat Free Mass/day) low energy availability (LEA) on exercise performance and physiological parameters related to health and training adaptations in female athletes. The latter is based on the prevalence of LEA being higher among female athletes, and most of the research is conducted on this population. In addition, we briefly address emerging evidence on short-term severe LEA in male athletes to highlight potential sex differences in physiological responses and performance outcomes. Short-term severe LEA triggers energy-conserving responses, leading to disruption in several crucial physiological systems, including suppression of the hypothalamic-pituitary-ovarian axis, decrease in triiodothyronine and insulin-like growth factor I hormones, reduction in resting metabolic rate, and comprised protein turnover in collagen-rich tissues. If these detrimental effects of short-term severe LEA are not reversed, they can progress to long-term problematic LEA, resulting in hypothalamic amenorrhea, lowering of bone mineral density, increased injury risk, and impaired exercise performance. Recent studies further underscore the detrimental impact of short-term severe LEA in female athletes, revealing suppressed muscle protein synthesis, increased cortisol levels, altered immune function, enhanced fat utilization during exercise, and direct impairments in power, sprinting, and endurance exercise performances despite reductions in body mass. These findings highlight the concerns about the trade-offs between short-term severe LEA for body mass reduction and the ability to maintain optimal physiological function for exercise performance. Further, they challenge the widespread assumption that body mass reduction always improves exercise performance, emphasizing a need for case-by-case considerations within the sporting environment.